FREQUENCY OF CORONARY ARTERY ANOMALIES IN ADULT CARDIOLOGY PRACTICE; AN ANGIOGRAPHIC STUDY - Shah, Ibrahim; Faheem, Mohammad; ., Shahzeb; Hafizullah, Mohammad; ., Rafiullah (Journal of Postgraduate Medical Institute, 2013)
Objective: The aim of this paper was to measure the frequency of various coronary artery anomalies in ourpatient population who underwent coronary angiography for various indications. Methodology: The data was collected retrospectively by analyzing the angiographic data of 13,615consecutive patients undergoing coronary angiography between January 2008 and June 2012. Results: Coronary artery anomalies were found in 305 patients (prevalence of 2.2 %). Among thesepatients, 186 (61.12%) were male and 119(39%) were female. Two hundred and ninety two (95.7%)anomalies were benign and 13(4.2%) were potentially of dangerous nature. Anomalies of the rightcoronary artery (RCA) in decreasing order of frequency included ectopic RCA from right sinus of valsalva(RSV) 54 (17.7%), coronary ectasia /aneurysm 24(7.8%), fistula 13(4.2%), RCA from left sinus of valsalva(LSV) with anomalous course 11(3.6%) and split RCA 3 (0.98%). Anomalies of the left coronary artery(LAD) in decreasing order of frequency included myocardial bridge 71(23.3%), separate origin of LAD andcircumflex from LSV (absent left main trunck) 58(19.02%), circumflex arising from RSV with anomalouscourse 28(9.18%), coronary ectasia/ aneurysm 23(7.54%), fistula 14(4.5%), LAD arising from RSV withanomalous course 3(0.98%), LCA arising from RSV with anomalous course(retroaortic) 1(0.32%) andsingle coronary artery 2(0.66%). Conclusion: The prevalence and the pattern of coronary artery anomalies in our patient population werealmost identical to previous studies. Cardiologists should be aware of the coronary anomalies because ofits potential for serious cardiac events and its importance in interventional cardiology and cardiac surgerypractice.